Identifikasi Kesalahan Siswa dalam Menyelesaikan Soal pada Materi Relasi dan Fungsi Kelas VIII SMP Negeri 2 Palangka Raya - Pradisa Anastasia; Sugiharto Sugiharto; Rizki Nurhana Friantini (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2026)
This study is motivated by the fact that most students still make many errors in solving problems on the topic of Relations and Functions. The purpose of this study is to determine: (1) the types of errors made by students in solving problems on Relations and Functions in class VIII-6 of SMP Negeri 2 Palangka Raya and (2) the factors causing these errors. This research is a descriptive study using a qualitative approach. The data source consists of 29 students, with 3 students selected for interviews. Data were collected through written tests and interviews. The test consisted of 5 essay questions that had been validated by 3 raters. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The results show that students' errors include: (a) factual errors, such as mistakes in writing symbols, function formulas, Cartesian diagrams, and set elements; (b) conceptual errors, such as misunderstanding relations and functions, inability to distinguish between relations and functions as well as domain and codomain; (c) operational errors, namely errors in calculations; and (d) principle errors, namely mistakes in applying formulas and writing final answers. The causes of errors are viewed from (a) remembering, (b) understanding, and (c) applying, which indicate a lack of mastery of prerequisite material and conceptual understanding. Keywords: Identification, Errors, Relations and Functions.